Pro-Palestinian netizen cyber activism through the Julid Fi Sabilillah movement on Instagram - Amrullah, Haekal Fajri; Bate, Andi Pajolloi; Briandana, Rizki (Islamic Communication Journal, 2024)
This study investigates the Julid Fi Sabilillah movement, a pro-Palestinian cyber activism initiative on Instagram formed by Indonesian netizens in response to the Al-Aqsa Hurricane attack by Israel. The emergence of a social movement on social media called Julid Fi Sabilillah became a mutually supportive virtual community that was formed to fight Israeli propaganda and its supporters on social media by trolling, cursing, and terrorizing the social media accounts of Israeli supporters. This research aims to find out and analyze how Julid Fi Sabilillah's activism on Instagram social media creates propaganda and mental attacks and creates negative issues for Israeli supporters on social media. Using a qualitative approach and case study method, this research revealed that the Julid Fi Sabilillah movement successfully countered the narrative supporting Israel on Instagram. Findings reveal that the movement has effectively disrupted pro-Israel accounts, causing psychological distress among supporters and amplifying global awareness of Palestine's plight. This digital activism highlights the potential of social media in uniting global efforts toward political and humanitarian causes. ***** Penelitian ini menyelidiki gerakan "Julid Fi Sabilillah", sebuah inisiatif aktivisme siber pro-Palestina di Instagram yang dibentuk oleh warganet Indonesia sebagai respons terhadap serangan Badai Al-Aqsa oleh Israel. Munculnya gerakan sosial di media sosial yang bernama Julid Fi Sabilillah menjadi komunitas virtual yang saling mendukung yang terbentuk karena adanya tujuan melawan propaganda Israel dan pendukungnya di media sosial dengan cara trolling menghujat dan meneror akun media sosial pendukung Israel. Penelitian ini bertujuan untuk mengetahui dan menganalisis bagaimana aktivitisme Julid Fi Sabilillah di media sosial Instagram dalam membuat propaganda, menyerang mental dan membuat isu negatif bagi pendukung Israel di media sosial. Dengan pendekatan Kualilatif dan metode studi kasus penelitian ini mengungkap bahwa gerakan Julid Fi Sabilillah berhasil melawan narasi pendukung Israel di Instagram. Hasil penelitian menunjukkan bahwa gerakan tersebut telah secara efektif mengacaukan akun-akun pro-Israel, menyebabkan tekanan psikologis di antara para pendukung dan meningkatkan kesadaran global akan penderitaan Palestina. Aktivisme digital ini menyoroti potensi media sosial dalam menyatukan upaya global menuju tujuan politik dan kemanusiaan.